Problems of the crisis of spatial design of art events in conditions of military aggression (Ukrainian experience) - Kucher, Rostyslav; Vakulenko, Daryna; Boiko, Valeriia; Roman, Roman; Dokolova, Alona (Convergences - Journal of Research and Arts Education, 2024)
Rethinking the processes accompanying spatial design from the correlation of the environment to the social, material, and spiritual aspects of its creation produce driving systems, even in the crisis period of wartime. In this regard, the study of the spatial design of art events is an urgent issue that requires a thorough study of the trends in the adaptation of spatial design to the modern demands of the artistic space of Ukraine. The purpose of the scientific work is to study the phenomenon of “spatial design”, as well as to study the problems of the crisis, in particular, the Ukrainian design of the space of the events of the artistic direction in the realities of martial law. To study the issues of the crisis state of the spatial design of Ukrainian artistic events, the method of analysis, the descriptive method of research, and the survey were used. As a result of the scientific research, the real state of the crisis of spatial design of artistic activities in Ukraine was studied and analysed, as well as the focus of the vision and trends introduced in the field of spatial design in the conditions of war were studied and described. The development of digital technologies and their use in the field of design has greatly reduced the material and time costs associated with the mobility of planning and creating a project of artistic space, but in order to create a universal modern project of spatial design of artistic events, the designer needs to understand the context of wartime. That is why the comfort of the atmosphere, where people will feel safe and comfortable, is one of the main requirements for the space of artistic events that take place during military operations. In the scientific work, in addition to studying the issues of the crisis of spatial design of Ukrainian art events, the requests of visitors to art events in Ukraine were investigated using a survey. Based on the answers and the wartime context, the main requirements for the spatial design of artistic events in Ukraine under the conditions of military aggression from Russia were formed.